2018
DOI: 10.1161/jaha.117.007809
|View full text |Cite
|
Sign up to set email alerts
|

Preterm Delivery and Future Risk of Maternal Cardiovascular Disease: A Systematic Review and Meta‐Analysis

Abstract: BackgroundPreterm delivery (<37 weeks gestational age) affects 11% of all pregnancies, but data are conflicting whether preterm birth is associated with long‐term adverse maternal cardiovascular outcomes. We aimed to systematically evaluate and summarize the evidence on the relationship between preterm birth and future maternal risk of cardiovascular diseases.Methods and ResultsA systematic search of MEDLINE and EMBASE was performed to identify relevant studies that evaluated the association between preterm bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
133
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(141 citation statements)
references
References 102 publications
2
133
1
5
Order By: Relevance
“…In the remaining two‐thirds, the onset of labor is spontaneous and impaired placentation has also been implicated as the underlying pathophysiology. A growing body of evidence, synthesized in systematic reviews, has demonstrated that women who deliver preterm, spontaneously or medically‐indicated, are at a greater risk of developing CVD …”
Section: Placental Syndromesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remaining two‐thirds, the onset of labor is spontaneous and impaired placentation has also been implicated as the underlying pathophysiology. A growing body of evidence, synthesized in systematic reviews, has demonstrated that women who deliver preterm, spontaneously or medically‐indicated, are at a greater risk of developing CVD …”
Section: Placental Syndromesmentioning
confidence: 99%
“…The latest systematic review and meta‐analysis of 21 studies including over 5.8 million women (out of whom more than 338 000 women had a history of preterm birth) demonstrated that preterm birth was associated with an increased adjusted risk of future CVD (RR 1.43; 95% CI, 1.18–1.72), CVD mortality (RR 1.78; 95% CI, 1.42–2.21), coronary heart disease (RR 1.49; 95% CI, 1.38–1.60), coronary heart disease mortality (RR 2.10; 95% CI, 1.87–2.36), and stroke (RR 1.65; 95% CI, 1.51–1.79) . Most importantly, the highest risk occurred when preterm birth occurred before 32 weeks of pregnancy or was medically indicated.…”
Section: Placental Syndromesmentioning
confidence: 99%
“…De novo hypertensive disorders of pregnancy and gestational diabetes mellitus (GDM) are recognized as risk factors for premature maternal CVD 2. Evidence has also been accumulating on maternal CVD associated with other pregnancy‐related complications and outcomes,3 such as preterm delivery,4, 5, 6, 7, 8, 9, 10, 11 fetal growth restriction5, 7, 10, 12 placental abruption,13 and pregnancy losses 5, 14, 15, 16…”
Section: Introductionmentioning
confidence: 99%
“…However, there is some evidence that preterm delivery could be associated with an increased risk of future maternal cardiovascular health. A recent systematic review and meta‐analysis has been published, in which information related to preterm delivery and the risk of maternal cardiovascular disease has been included. The authors included only cohort studies with a low risk of bias and they excluded patients who had had cardiovascular disease before or during pregnancy.…”
Section: Preterm and The Maternal Risk Of Cardiovascular Diseasementioning
confidence: 99%
“…Sensitivity analyses were performed to consider the effect of pregnancy duration, recurrence, and spontaneous onset of preterm delivery on maternal cardiovascular outcomes. The authors found that the risks were higher when preterm deliveries occurred before 32 weeks of pregnancy or among those deliveries with medical indications such as fetal growth or pre‐eclampsia …”
Section: Preterm and The Maternal Risk Of Cardiovascular Diseasementioning
confidence: 99%